Isolation and molecular characterization of symbiotic bacterial isolates associated with entomopathogenic nematodes in agro climatic zone 5 of Karnataka - Vinay Kumar, S; Mulla, S R; Suresh, C K (Journal of Phytology, 2011)
The investigation was carried out to study the biochemical characterization of symbiotic bacteria associated with entomopathogenic nematodes isolated from agro climatic zone 5 of Karnataka. Twenty two entomopathogenic nematodes were isolated by insect bait method using fifth instar larvae of Galleria mellonella. Twenty symbiotic bacteria were isolated from these entomopathogenic nematodes and named based on the source place. These isolates were identified based on microscopic observation, biochemical and physiological characters like Gelatin liquefaction test, Catalase test, Lactose fermentation test, Urease test, Motility test and Colony morphology studies on Nutrient agar, NBTA and Mac Conkey agar media. The diversity of these isolates was characterized by using RAPD markers. Primer screening was carried out using 13 decamer random primers, out of which 7 primers were detected for RAPD analysis. A total of 44 bands were scored out of which 42 bands were found to be polymorphic. Statistical analysis of RAPD data clearly depicted that all the 20 symbiotic bacterial isolates formed four major clusters. The percent polymorphism observed in the isolates was 95.45% which is quiet high and suggests that the symbiotic bacterial population exhibit high genetic diversity.